2006
DOI: 10.1016/j.jbusres.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Customer orientation, conflict, and innovativeness in Japanese sales departments

Abstract: There has been an argument over whether customer orientation enhances innovation; moreover, the customer orientation/innovation mechanism remains unclear. This study investigated how customer orientation influences innovativeness through three types of conflict using a sample of 193 sales departments in Japanese firms. A structural equation modeling revealed that (1) customer orientation was positively related to task conflict and negatively related to process conflict, and that (2) task conflict was positivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
98
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 58 publications
(124 reference statements)
5
98
0
7
Order By: Relevance
“…While Jehn et al (1999) proposed that process conflict would be beneficial due to the better fit between individual ability and task requirements expected, they found that high levels of process conflict deterred constructive task discussions and actual implementation. Consistent with what we found regarding process conflict norms, much of the empirical work examining process conflict has found that it negatively influences processes affecting performance (Behfar et al 2002;Greer and Jehn 2007;Porter and Lilly 1996;Vodosek 2005) and innovation (Matsuo 2006). The open norms encouraging process conflict discussions may have incited issues of disrespect regarding members' abilities and competency in process decisions, and similar to the findings of Jehn et al (1999), apparently interfered with effective task accomplishment.…”
Section: Discussionsupporting
confidence: 81%
“…While Jehn et al (1999) proposed that process conflict would be beneficial due to the better fit between individual ability and task requirements expected, they found that high levels of process conflict deterred constructive task discussions and actual implementation. Consistent with what we found regarding process conflict norms, much of the empirical work examining process conflict has found that it negatively influences processes affecting performance (Behfar et al 2002;Greer and Jehn 2007;Porter and Lilly 1996;Vodosek 2005) and innovation (Matsuo 2006). The open norms encouraging process conflict discussions may have incited issues of disrespect regarding members' abilities and competency in process decisions, and similar to the findings of Jehn et al (1999), apparently interfered with effective task accomplishment.…”
Section: Discussionsupporting
confidence: 81%
“…A review of numerous researches shows that this relationship remains controversial. Indeed, some studies ISSN 2157-6068 2014 provided evidence that innovation has a positive effect on organizational performance (Bierly and Chakrabarti, 1996;Caves and Ghemawat, 1992;Darroch, 2005;Matsuo, 2006). However, others found negative relationship (Balkin et al, 2000) or instead no significant relationship between these variables (Greve, 2003).…”
Section: Contributions Of Innovation To Organizational Performancementioning
confidence: 99%
“…Lysonski & Johnson, 1983;Matsuo, 2006). Relationship selling, as a paradigm, has propagated a belief that with the right training and tools, sales people can suspend or even suppress a market by creating and maintaining strong and enduring relationships with their customers (Tzokas, Saren & Kyziridis, 2001;Ahearne, Bhattacharya & Gruen, 2005).…”
Section: Introductionmentioning
confidence: 99%